Pertanggungjawaban Pidana Pelaku Cyberstalking Sebagai Bentuk Kekerasan Seksual Berbasis Elektronik: Studi Putusan Nomor 1842/Pid.Sus/2024/PN Sby - Bella Mayasari; Erny Herlin Setyorini (JURNAL ILMIAH NUSANTARA, 2026)
The rapid evolution of information technology has triggered the emergence of a new form of crime, namely electronic-based sexual violence, where cyberstalking is one manifestation that can cause deep psychological trauma for survivors even though there is no direct physical interaction. This study focuses on elaborating and analyzing the criminal liability framework and evidentiary mechanisms for the crime of electronic sexual violence as stipulated in Decision No. 1842/Pid.Sus/2024/PN Sby. The research design adopted is a normative juridical method by integrating statutory, conceptual, and case analysis approaches. Legal facts were found that the defendant's obligation to bear criminal consequences was legally valid due to his status as a legally responsible subject, as well as the existence of malicious intent or dolus when sending messages and manipulating sexual images through an artificial intelligence application, in addition to the lack of justification or excuse found. The verdict was handed down by the panel of judges with reference to Article 14 of Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence. Regarding the evidence, the judge's conviction was built through a comprehensive synergy between electronic evidence with witness testimony, expert explanations, and psychological evaluation results that confirmed the presence of anxiety disorders, depression, and Post Traumatic Stress Disorder, as per the principle of the negative evidence system mandated by Article 183 of the Criminal Procedure Code. The recommendation proposed in this study is the importance for law enforcement officers to pay more in-depth attention to the psychological impact experienced by victims and to strengthen digital forensic capabilities in managing electronic-based sexual crime cases.